Foliar Fungicides Containing FRAC 11 Mitigate Phomopsis Stem Canker in Sunflower (Helianthus annuus) - Dangal, Nabin K (Plant disease, 2023)
Phomopsis stem canker reduces yield of sunflower (Helianthus annuus L.) up to or exceeding 40%; however, management recommendations have not been developed for U.S. farmers. Between 2009 and 2020, foliar fungicide trials were conducted in Minnesota, Nebraska, North Dakota, and South Dakota for a total of 49 location-years. Random effects meta-analyses were performed on the disease severity index (DSI) and yield data collected from the foliar fungicide trials to determine the overall and individual effectiveness of the tested fungicides. Effect sizes, Cohen's f or Hedges' g, were calculated as the difference in DSI or yield between the fungicide treatment and nontreated control (NTC) divided by the pooled SD. The pooled Cohen's f for DSI and yield was 0.40 (95% CI = [0.29, 0.42]), indicating a large effect size and that fungicide treatments had a significant effect on DSI and yield (P < 0.0001). Among the fungicide groups, quinone outside inhibitor (QoI) (DSI [k = 45; g = -0.47] and yield [k = 46; g = 0.41]) is moderately effective and premixes of demethylation inhibitors (DMI), succinate dehydrogenase inhibitors (SDHI), and QoI (DMI + SDHI + QoI) (DSI [k = 3; g = -0.79] and yield [k = 3; g = 0.94]) are largely effective in comparison with NTC. Upon performing prediction analyses, the probability of not recovering the fungicide application cost (Ploss) associated with QoI (pyraclostrobin) was <0.35 for a range of sunflower grain prices suggesting a greater probability of return on investment from a single application of fungicide. Overall, our study suggests that the use of QoI fungicides is likely to be profitable in the presence of Phomopsis stem canker (DSI > 5%)